2018
DOI: 10.1093/ons/opx291
|View full text |Cite
|
Sign up to set email alerts
|

Radiofrequency Energy and Electrode Proximity Influences Stereoelectroencephalography-Guided Radiofrequency Thermocoagulation Lesion Size: An In Vitro Study with Clinical Correlation

Abstract: Radiofrequency lesions produced using low-energy delivery between SEEG electrodes in close proximity can produce a large lesion. These findings might have advantages for treatment of focal epilepsy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 18 publications
0
19
0
Order By: Relevance
“…The French national guidelines on SEEG include a section dedicated to SEEG-guided RF-TC and are, to date, the only recommendations published on this topic [40,41]. They slightly differ from the initial description of the technique [18] as more recent laboratory investigations have found that two parameters determine the volume of the lesion: the dipole selection and the radiofrequency parameters [42,43].…”
Section: Radiofrequency Thermocoagulationmentioning
confidence: 99%
“…The French national guidelines on SEEG include a section dedicated to SEEG-guided RF-TC and are, to date, the only recommendations published on this topic [40,41]. They slightly differ from the initial description of the technique [18] as more recent laboratory investigations have found that two parameters determine the volume of the lesion: the dipole selection and the radiofrequency parameters [42,43].…”
Section: Radiofrequency Thermocoagulationmentioning
confidence: 99%
“…Counterintuitively, larger lesions across electrodes were created at a lower power (3 watts) even if contacts of the two electrodes were 8-12 mm apart. Once a rise in tissue impedance was seen, no further enlargement of the lesion was noted despite the continued application of current for up to 180 s. 27 In the same study, in vivo application revealed similar results. Three patients underwent SEEG-based RF-TC and larger lesions were noted with an application of 3 watts, albeit with more perilesional edema which may not be desirable within or near eloquent regions.…”
Section: Discussionmentioning
confidence: 60%
“…22) A recent study suggested the possibility of generating a larger lesion by delivering lower power of current (<3 W), which may contribute to a better outcome in SEEG-guided RF-TC. 59)…”
Section: Seeg-guided Rf-tcmentioning
confidence: 99%